Torque Differential-Based Dynamic Modeling, Validation, and Steering Characteristics Analysis of Multi-Axial Skid-Steered Wheeled Vehicle - Yuzheng Zhu; Shihua Yuan; Xueyuan Li; Ao Li; Xin Gao (Actuators)
Skid-steered technology has been widely applied to wheeled vehicles due to its advanced pivot steering capabilities and adaptable power transmission systems. To better understand the steering characteristics of skid-steered wheeled vehicles and derive general conclusions, a torque differential-based (TD-based) two-degree-of-freedom (2-DOF) dynamic model was developed. This model is grounded in the vehicle’s steering mechanism and the single-wheel dynamics model, and a steering radius model based on TD input was established using the concept of the instantaneous center of rotation (ICR). Additionally, an expression for the stability factor was derived, and both the steady-state and transient steering characteristics were analyzed. Finally, the real vehicle tests demonstrated that the TD-based dynamic model responds quickly, maintains high precision, and remains stable across different steering input frequencies. Compared with the SD-based dynamic model, the TD-based dynamic model has a 2.553% higher calculation accuracy for the steering radius, a 6.251% higher comprehensive response accuracy for the steering input, and a response speed advantage of 1.035%.